Juridical Review of the Protection of Victims of Domestic Violence Based on Law Number 23 of 2004 - Rahma Dita A. Muda (Judge : Jurnal Hukum, 2025)
This study aims to examine juridically the form of protection for victims of domestic violence (KDRT) based on the provisions of Law Number 23 of 2004. The approach used in this study is normative-empirical, by utilizing primary and secondary data that are relevant to the study topic. The results of the study show that the forms of legal protection provided to victims of domestic violence include partnerships with related agencies, such as social services and women and child protection institutions, as well as through the mediation process or direct facilitation to victims. However, there are various obstacles that reduce the effectiveness of these protection efforts. One of the main obstacles is the tendency of victims to retract reports and refuse legal proceedings against the perpetrators, which hinders firm action from the police. This phenomenon shows that there is still low legal awareness among victims and emotional dependence on perpetrators. This research emphasizes the importance of increasing education to the public about the dangers and impacts of domestic violence, as well as the need for stronger synergy between the Women and Children Service Unit (PPA), the Women's Empowerment and Child Protection Office (P3A), and the Social Service. In addition, the provision of adequate protection facilities is also considered important to support victims in undergoing legal proceedings. It is hoped that the results of this research can contribute to the formation of more effective and responsive policies for the protection of victims of domestic violence, especially in the Gorontalo City Police area.